THE ROLE AND PLACE OF FINANCIAL MONITORING IN THE SYSTEM OF PUBLIC FINANCIAL CONTROL - Shvets, Nataliya; Akrytov, Andriy (Socio-economic relations in the digital society, 2020)
In the presented article the authors conduct a scientific and methodological study of the role and place of the system of prevention and counteraction to legalization (laundering) of proceeds from crime, terrorist financing and financing the proliferation of weapons of mass destruction in the system of public financial control.Based on the results of the study, the authors consider control as one of the methods of state-authorized bodies in the implementation of supervisory and control form of state functions, which is manifested in systematic monitoring and verification of the operation of the object of a social, industrial or other process. authorized persons in order to counteract something undesirable, detection, prevention and cessation of illegal behavior by the object of observation.State financial control is defined by the authors in the article as the activities of public authorities and management within the control and supervisory form of state functions, which is represented by a set of forms, methods and tools of control by which these bodies receive information about the actual state of affairs, distribution and use of public financial resources at all levels of the public sector of the economy in order to detect, prevent and stop illegal behavior by the object of observation.In the context of the author’s vision, the study presents a logical chain of interrelation of the concepts of «financial control», «public financial control», «countering the legalization of illegal income». The emphasis is on the author’s view on financial monitoring as a subsystem of a holistic system of combating money laundering in the state. The methodological approach to the functioning of counteraction to money laundering is substantiated, according to which financial monitoring is considered more as an element of state financial control and to a lesser extent as an element of financial control (in terms of primary financial monitoring that can be carried out by non-governmental bodies).
Keywords: state’s functions; state financial control; financing of criminal activity; proceeds of crime; financial monitoring